Rural Study Series - Banu, Dilruba; Khan, Md Kaisar Ali; Chowdhury, A. Mushtaque R.; Karim, Fazlul; Streefland, Pieter; Ahmed, Salehuddin; Afsana, Kaosar; Ali, Ahmed; Mahmud, Shah Noor (BRAC Research and Evaluation Division, 2022)
The Rural Study Series is a modest venture for dissemination of BRAC research studies concerned with various aspects of rural development in Bangladesh. Poverty alleviation and empowerment of the poor, particularly of the disadvantaged women are the two major goals of BRAC. Since 1972, BRAC has been implementing a multi-sectoral programme to achieve these objectives. BRAC deals with people whose lives are characterized by absolute poverty, illiteracy, unemployment, disease and malnutrition. The underlying conviction in its development approach is founded on the premise that it is the people who can bring about change in their own lives, either individually or collectively, supported by inputs provided by development agencies, including BRAC. The Research and Evaluation Division (RED), instituted in 1975, is an independent unit within BRAC and it plays a vital role in planning, strategy formulation, monitoring and evaluation of BRAC's development interventions. Its primary responsibility is to provide necessary research support to various BRAC programmes. RED conducts a wide range of research, which includes, among others, surveys, action research, diagnostic studies, impact assessment and evaluation studies on poverty alleviation. In addition, it undertakes studies on request from other NGOs, government organizations, international development agencies, as well as joint studies with academic and research institutions, both in and outside of Bangladesh. The Rural Study Series emphasizes policy relevance and operational features of BRAC's programmes at grassroots level, rather than theoretical and rigid methodological issues. BRAC, in previous years, published several monographs on development issues (list available at the back of this volume). This new series will cover selected research studies, which have been carried out since 1990. The views and interpretations presented in the Series are those of the author(s) and do not necessarily represent the views and policies of BRAC. Comments or brief notes responding to articles are welcome and will be considered for publication to the extent that space permits. Please direct all correspondence to the Editor, The Rural Study Series, BRAC, 66 Mohakhali C/A, Dhaka 1212, Bangladesh.